1984
DOI: 10.1001/archderm.120.12.1591
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone photosensitivity

Abstract: Amiodarone hydrochloride is currently being investigated in the United States as a cardiac antiarrhythmic agent. Previous reports from Europe indicate that amiodarone occasionally causes a cutaneous photosensitivity reaction that may be associated with a peculiar blue-gray discoloration of the skin. In addition, corneal microdeposits of yellow-brown granules may occur. We report observations on a case of amiodarone photosensitivity and corneal deposits developing in a patient shortly after amiodarone therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The administration of amiodarone is accompanied by a relatively large number of cutaneous side-effects. The incidence of photosensitivity in this study was 50%, a figure closely in agreement with previous reports in the United Kingdom (Chalmers et ah, 1982) and in the United States of America (Walter, Bradner & Curtis, 1984). This high level of cutaneous involvement is strongly suggestive of a phototoxic reaction, as was the clinical presentation of burning erythema without any accompanying dermatitis.…”
Section: Discussionsupporting
confidence: 92%
“…The administration of amiodarone is accompanied by a relatively large number of cutaneous side-effects. The incidence of photosensitivity in this study was 50%, a figure closely in agreement with previous reports in the United Kingdom (Chalmers et ah, 1982) and in the United States of America (Walter, Bradner & Curtis, 1984). This high level of cutaneous involvement is strongly suggestive of a phototoxic reaction, as was the clinical presentation of burning erythema without any accompanying dermatitis.…”
Section: Discussionsupporting
confidence: 92%
“…7 The photoactivating wavelengths are primarily found in the long-wave UV-A spectrum between 350 and 380 nm. 8 However, phototests may show acute reactions to UV-A and UV-B and significant delayed reactions to UV-A and/or UV-B. 4,9 Zinc oxide-containing preparations appear to be the most effective agents for reducing cutaneous photosensitivity.…”
Section: Commentmentioning
confidence: 99%
“…6 It was demonstrated that these granules are found in skin and corneal deposits, and activated by sun exposure. 7 The reported incidence of amiodarone phototoxicity is noted to be 10% in patients on unprotected sun exposed areas. 8 Autopsy studies have demonstrated higher concentrations of amiodarone and desethyl-amiodarone in pigmented than in unpigmented skin.…”
Section: Discussionmentioning
confidence: 99%